Trajectories of childhood body mass index are associated with adolescent sagittal standing posture - Smith, Anne; O'Sullivan, Peter; Beales, Darren; de Klerk, N.; Straker, Leon (Informa Healthcare, 2011)
Objectives. To identify distinct age-related trajectory classes of body mass index (BMI) z-scores from childhood to adolescence, and to examine the association of these trajectories with measures of standing sagittal spinal alignment at 14 years of age. Methods. Adolescents participating in the Western Australian Pregnancy Cohort (Raine) Study contributed data to the study (n=1 373). Age- and gender-specific z-scores for BMI were obtained from height and weight at the ages of 3, 5, 10 and 14 years. Latent class group analysis was used to identify six distinct trajectory classes of BMI z-score. At the age of 14 years, adolescents were categorised into one of four subgroups of sagittal spinal posture using k-means cluster analysis of photographic measures of lumbar lordosis, thoracic kyphosis and trunk sway. Regression modeling was used to assess the relationship between postural angles and subgroups, and different BMI trajectory classes, adjusting for gender. Results. Six trajectory classes of BMI z-score were estimated: Very Low (4%), Low (24%), Average (34%), Ascending (6%), Moderate High (26%) and Very High (6%). The proportions of postural subgroups at age 14 were; Neutral (29%), Flat (22%), Sway (27%) and Hyperlordotic (22%). BMI trajectory class was strongly associated with postural subgroup, with significantly higher proportions of adolescents in the Very High, High and Ascending BMI trajectory classes displaying a Hyperlordotic or Sway posture than a Neutral posture at age 14. Conclusions. This prospective study provides evidence that childhood obesity, and how it develops, is associated with standing sagittal postural alignment in adolescence.